ANALISIS VONIS BUI JURNALIS PT AURORA MEDIA UTAMA BERDASARKAN PUTUSAN NOMOR 46/PID.SUS/2021/PN PLP - Holik, Tubagus Abdul; Iman, Candra Hayatul (Jurnal Ilmiah Wahana Pendidikan, 2023)
Abstract A journalist seeks news from trusted sources and is expected to report objectively in accordance with the facts on the ground and does not have a certain point of view in serving the community. This research method uses normative juridical in the form of primary data, in the form of rules and secondary data in the form of official legal documents that have been published, in analyzing the study using content analysis techniques. The results of the discussion and conclusions from this research, that the process of resolving press cases based on laws that can be used by readers or the public against journalistic products, namely using the right of reply and right of correction then for complaints submitted by the public can be submitted to the press council. The verdict that was read out by the judge for the defendant for defamation was appropriate because all the elements in the indictment article had been fulfilled and the settlement process was in accordance with applicable regulations. Press institutions and journalists must follow the guidelines and principles of writing so that press freedom does not injure the human rights of others. Keywords: Press, Journalists, Defamation